Celibacy in Algeria: causes and consequences - khadra Rachedi (Social Empowerment Journal, 2021)
Current research aims to show the reality, causes and effects of celibacy in Algeria. Numerous studies have highlighted the alarming rise in celibacy due to unemployment, the housing crisis, the high cost of dowry and marriage costs, the high level of education of women, their years of schooling and their access to work.      On the basis of a series of data, it has been shown that the proportion of single people has increased significantly in both sexes, particularly among women, resulting in a higher age of marriage, a worsening of spinsterhood, and the emergence of new types of families that can affect social harmony. Therefore, one of the research proposals is to provide psychological and material support to young people to encourage them to marry